Searching for gravitational-wave bursts from cosmic string cusps with the Parkes Pulsar Timing Array. Issue 1 (2nd December 2020) - Yonemaru, N; Kuroyanagi, S; Hobbs, G; Takahashi, K; Zhu, X-J; Coles, W A; Dai, S; Howard, E; Manchester, R; Reardon, D; Russell, C; M Shannon, R; et al.
ABSTRACT: Cosmic strings are potential gravitational-wave (GW) sources that can be probed by pulsar timing arrays (PTAs). In this work we develop a detection algorithm for a GW burst from a cusp on a cosmic string, and apply it to Parkes PTA data. We find four events with a false alarm probability less than 1 per cent. However further investigation shows that all of these are likely to be spurious. As there are no convincing detections we place upper limits on the GW amplitude for different event durations. From these bounds we place limits on the cosmic string tension of G μ ∼ 10 −5, and highlight that this bound is independent from those obtained using other techniques. We discuss the physical implications of our results and the prospect of probing cosmic strings in the era of Square Kilometre Array.